Analysis Of Regional Fixed Assets Management In Buton District Financial And Regional Assets Agency - Bahari, Samsul (International Journal of Management Progress, 2022)
This research was conducted at the Regional Finance and Assets Agency (BKAD) of South Buton Regency. This study aims to determine and provide an overview of the Analysis of Regional Fixed Asset Management at the Regional Finance and Agency (BKAD) of South Buton Regency. This type of research is comparative, the type of data used is qualitative data with data sources, namely primary data and secondary data. Data collection methods include field research (fieldnote research) and library research (library research). The data obtained is then analyzed using the comparative method, which is a method or procedure in the form of numbers that compares the budget data with the realization data. The results of the research and discussion show that Permendagri No. 19 of 2016 concerning Technical Guidelines for the Management of Regional Finance and Assets Agency (BKAD) of South Buton Regency.